Card15 gene overexpression in mononuclear and epithelial cells of the inflamed Crohn's disease colon. Issue 6 (1st June 2003) - Berrebi, D; Maudinas, R; Hugot, J-P; Chamaillard, M; Chareyre, F; De Lagausie, P; Yang, C; Desreumaux, P; Giovannini, M; Cézard, J-P; Zouali, H; Emilie, D; et al.
Abstract : Background: Crohn's disease is one of the principal human chronic inflammatory bowel diseases. Although its aetiology is still unknown, its complex pathogenesis has environmental, immunological, and genetic determinants. CARD15 is the first susceptibility gene implicated in the predisposition to Crohn's disease and is known to be expressed only in monocytes. However, its expression in situ has not yet been studied. Aims: To analyse the tissue distribution of CARD15 and identify cells producing CARD15 in samples of colon from patients with Crohn's disease and control subjects. Patients and methods: We analysed CARD15 gene expression in surgical specimens of colon from eight children with Crohn's disease and nine controls by immunohistochemistry, in situ hybridisation, and reverse transcription-polymerase chain reaction (RT-PCR). Results: We showed that CARD15 was present only in the cytoplasm of macrophages in the normal colon. Increased CARD15 expression was detected in Crohn's disease lesions. There were more CARD15 positive cells in Crohn's disease lesions than in uninvolved areas. Both intestinal epithelial cells, macrophages, and their derivatives overproduced CARD15 in Crohn's disease. To further assess CARD15 expression by intestinal epithelial cells, we performed RT-PCR on freshly isolated intestinal epithelial cells, and showed that these cells isolated from Crohn's disease samples contained more CARD15 mRNA than intestinal epithelial cells from controls. Conclusions: We have demonstrated that colonic involvement in active Crohn's disease is associated with increased CARD15 gene expression in both macrophages and intestinal epithelial cells. Therefore, this deregulation can affect the host-environment interaction and thus contribute to the pathogenesis of this disease.